PENGARUH FREE CASH FLOW, STRUKTUR MODAL, DAN ASIMETRI INFORMASI TERHADAP MANAJEMEN LABA - Christabel, Nurainun Bangun (Jurnal Paradigma Akuntansi, 2020)
The research objective is to present empirical evidence of the effect of free cash flow, capital structure, and information asymmetry on earnings management in manufacturing companies listed on the Indonesia Stock Exchange in 2016-2018. Company samples used in this study were 39 companies. This research uses a purposive sampling techniqueand uses panel data assisted by the E-views 10+ program in data processing. T test results in this research indicate that free cash flow has a negative and significant effect on earnings management, while capital structure and information asymmetry have no significant effect on earnings management.